Kommunale Handlungsfähigkeit im europäischen Vergleich Autonomie, Aufgaben und Reformen - Kuhlmann, Sabine (Modernisierung des öffentlichen Sektors ("Gelbe Reihe"), 2021)
This book compares the roles of municipalities in Europe, using categories such as municipal autonomy, task profiles, territorial and political frameworks, and financial conditions. Past and present reform trends and discourses are also described and classified. The study constitutes a secondary analysis of existing empirical research and presents current figures from various sources. It was conducted by a team led by Prof. Sabine Kuhlmann from the Department of Political Science, Administration and Organisation at the University of Potsdam.